Extended reality visualization of medical museum specimens: Online presentation of conjoined twins curated by Dr. Jacob Henle between 1844-1852 - Brandi S. Mikami; Thomas E. Hynd; U-Young Lee; J. DeMeo; Jesse D. Thompson; Roman Sokiranski; Sara Doll; Scott Lozanoff (Elsevier, 2022)
Background: The purpose of this study is to characterize a full-term conjoined twins' cadaver curated by Dr. Jacob Henle sometime between 1844 and 1852 and demonstrate digital distribution of an old and rare medical museum specimen using an extended reality (XR) model workflow. Methods: The cadaver (Preparation 296) is in the Department of Anatomy and Cell Biology at the University of Heidelberg. An XR display workflow comprises image capture, segmentation, and visualization using CT/MR scans derived from the cadaver. Online radiology presentation to medical students focuses on diagnostic characteristics of anatomical systems depicted with XR models. Results: Developmental defects in Preparation 296 include duplicated supradiaphragmatic structures and abnormal osteological features. Subdiaphragmatically, the gut is continuous on the right, but terminates at the distal esophagus on the left. One large liver occupies the abdomen with one spleen located on the left side. Observations suggest duplication of the primitive streak and separate notochords rostrally. Duplication occurs near the yolk sac and involves midgut formation while secondary midline fusion of the upper extremities and ribs likely results from the proximity of the embryos during development. Medical students access the model with device agnostic software during the curricular topic "Human Body Plan" that includes embryology concepts covering mechanisms of twinning. Conclusions: The workflow enables ease-of-access XR visualizations of an old and rare museum specimen. This study also demonstrates digital distribution and utilization of XR models applicable to embryology education.